Pengaruh Headline Terhadap Minat Membaca Berita Pada Suara.Com (Studi Pada Mahasiswa Jurnalistik Angkatan 2018 Fakultas Dakwah Dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang) - Viky Pira Ranti; Aliasan; Hartika Utami Fitri (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
The development of media in the digital era is currently growing rapidly, one of which is the development of online media at this time. Online media that is currently in great demand, one of which is Suara.com. News is a journalistic product, journalist or journalism comes from the word journal, which means diary, or notes about daily events, or it could also mean newspapers. To attract the public's interest in reading the news, headlines must be made as good as possible. The headline is the big title of a work, the headline is located at the very top, and is the first thing the reader sees. Headlines are measured based on the following indicators: Duration, Frequency and Attention. Meanwhile, reading interest is measured by the following indicators: attention, interest, desire, and action.The approach used is quantitative with survey methods. The population in this study were 117 students in the Journalism Study Program, Faculty of Da'wah and Communication, UIN Raden Fatah Class of 2018, with a research sample of 12 students. Data collection techniques used in this study are questionnaires, documentation, and observation. The data analysis technique used in this study is the correlation regression test. Before the correlation regression test was carried out, validity and reliability tests were carried out first, as well as the classical assumption test. From the results of data analysis, the results show that there is a significant influence between the two variables, namely headlines on interest in reading news on Suara.com, it can be seen from the results t = 5.207 > t table and the significance is 0.000, so H0 is rejected H1 is accepted. And Headlines of 45.1% affect interest in reading news on Suara.com. This is evidenced by a correlation value of 0.451.